2004
DOI: 10.1079/bjn20041039
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum(‘Lingzhi’), a Chinese medicinal mushroom: biomarker responses in a controlled human supplementation study

Abstract: Lingzhi (Ganoderma lucidum) is a woody mushroom highly regarded in traditional medicine and is widely consumed in the belief that it promotes health and longevity, lowers the risk of cancer and heart disease and boosts the immune system. However, objective scientific validation of the putative health benefits of Lingzhi in human subjects is lacking, and issues of possible toxicity must be addressed. The present double-blinded, placebo-controlled, cross-over intervention study investigated the effects of 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(95 citation statements)
references
References 25 publications
1
74
0
4
Order By: Relevance
“…It is prescribed by herbalists not only as a general dietary/ health supplement and putative immunomodulator, but also for specific treatment of hypercholesterolemia, hypertension, asthma, and allergy. There is no conclusive evidence of dosedependent hemostatic impairment [46], renal or hepatic toxicity [100], or of genotoxicity/mutagenicity [13]. Occasional cases of watery diarrhea due to ingested Ganoderma spore overgrowth have been reported [102].…”
Section: Ganoderma Lucidum (Ling Zhi Rei Shi; 'Mushroom')mentioning
confidence: 99%
“…It is prescribed by herbalists not only as a general dietary/ health supplement and putative immunomodulator, but also for specific treatment of hypercholesterolemia, hypertension, asthma, and allergy. There is no conclusive evidence of dosedependent hemostatic impairment [46], renal or hepatic toxicity [100], or of genotoxicity/mutagenicity [13]. Occasional cases of watery diarrhea due to ingested Ganoderma spore overgrowth have been reported [102].…”
Section: Ganoderma Lucidum (Ling Zhi Rei Shi; 'Mushroom')mentioning
confidence: 99%
“…Wachtel-Galor et al, (2004) stated if G. lucidum could maintain the consumer's health. Analysis of Ganoderma lucidum by Stamets (2000) both qualitatively and quantitatively reported that Ganoderma lucidum contain different bioactive compounds which depend on its growth medium and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The basidiocarp, mycelia, and spores of G. lucidum contain approximately 400 different bioactive compounds with polysaccharides, peptidoglycans, and triterpenes being the three major physiologically active constituents [1]. The specific reported attributes of G. lucidum include lowering the risk of cancer, heart disease, and infection; these health-promoting effects are believed to be mediated through the antioxidant, hypotensive, anti-inflammatory, and immunomodulatory properties of the mushroom [2]. Modern uses of the mushroom therefore include treatment of coronary heart diseases, arteriosclerosis, hepatitis, arthritis, nephritis, bronchitis, asthma, hypertension, cancer, and gastric ulcer [3].…”
Section: Introductionmentioning
confidence: 99%